Successful Steroid Treatment of Extrahepatic Cholestasis: A Case Report - Setyoboedi, Bagus; Prihaningtyas, Rendi Aji; Irawan, Muhammad; Octariyandra, Syania Mega; Arief, Sjamsul (HM Publisher, 2024)
Background: Biliary atresia is the most common cause of cholestasis. However, not all healthcare facilities are capable of performing Kasai surgery and liver transplantation. The involvement of inflammatory processes in the bile ducts triggered by viral infections has been suggested in several theories of pathogenesis. This case report describes the successful steroid treatment of an infant with extrahepatic cholestasis. Case presentation: A girl aged 2 months and 20 days presented with complaints of jaundice since the age of 2 weeks, with no improvement and worsening of the jaundice, with the color of the stools becoming paler than before. The nutritional status is normal. The physical examination revealed icteric sclera, hepatomegaly, and splenomegaly. There was cholestasis (total bilirubin 7.30 mg/dL and direct bilirubin 5.75 mg/dL), as well as elevated levels of AST (249 U/L), ALT (251 U/L), GGT (995.7 U/L) and increased to 1529.6 U/L, CMV reactive IgG 28.9, and Rubella reactive IgG 6.90. A two-phase ultrasound of the abdomen showed a thickening of the gallbladder wall. A liver biopsy showed mild portal fibrosis (F1). Steroids at a dose of 2 mg/kg/day in combination with ursodeoxycholic acid were administered. At follow-up one month later, the jaundice had improved. Stools were yellow-brown, and liver function tests and bilirubin were normal. Conclusion: Adjunctive steroid therapy to suppress the inflammatory process in biliary obstruction may be beneficial in the early phase of the disease, especially in limited surgical and transplant settings.